Cheap but Flighty: How Global Imbalances create Financial Fragility - Enrico Perotti; Toni Ahnert (Tinbergen Institute, 2015)
Can a wealth shift to emerging countries explain instability in developed countries? Investors exposed to political risk seek safety in countries with better property right protection. This induces private intermediaries to offer safety via inexpensive demandable debt, and increase lending into marginal projects. Because safety conscious foreigners escape any risk by running in some good states, cheap foreign funding leads to larger and more frequent runs. Beyond some scale, foreign runs also induce domestic runs in order to avoid dilution. When excess liquidation causes social losses, a domestic planner may limit the scale of foreign inflows or credit volume.
Keywords: F3; G02; 330; capital flows; unstable funding; safe haven; absolute safety